Understanding the role of social support and social support network for depression among informal dementia caregivers: a pilot clinical project on caregivers in NYC. (21st October 2021) - Park, Daejun; Morano, Carmen; Savage, Andrea
ABSTRACT: This study aims to explore the association of depressive symptoms with the informal social support network reported by dementia caregivers participating in a community-based caregiver support program. Caregivers in a community-based dementia caregiver program completed an intake assessment, including the social support network instrument. Measures were completed for caregivers' social support network, using the social support network instrument (SSNI). Measures also included depression, caregiver strain, basic activities of daily living, instrumental activities of daily living, and demographics. Findings suggest the effects of social supports and social network on caregivers' depressive symptoms. Caregivers who had financial supports were less likely to have depressive symptoms. Also, the frequency of contact among social network variables predicted the decrease of depressive symptoms.